1996
DOI: 10.1108/eb010667
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting the Adoption of Employment Equity: An Example From Canada

Abstract: Historically, Canada has always been a diverse nation made up of a wide variety of different peoples. However, the nature, causes and manifestations of diversity have been changing, along with the attitudes towards the treatment of diversity within the country's social, economic and political structures. For example, the dominant organisational culture in business and government has traditionally been created by white, able‐bodied, Canadian‐ born males with shared values and behaviours (McDonald, 1991). Other … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 10 publications
1
9
0
Order By: Relevance
“…Consistent with strategic choice theory (e.g., Child 1972;Hrebiniak and Joyce 1985;Oliver 1991) and the premise that CEO leadership plays a pivotal role in the adoption of organizational diversity practices (e.g., Ng 2008;Mighty 1996), results from this study suggest that both CEO transformational and transactional leadership influence the extent to which organizational diversity practices are implemented in organizations. Specifically, transformational leadership was found to be directly positively associated with the implementation of organizational diversity practices, while the influence of transactional leadership on organizational diversity practices was moderated by the social values and age of the CEO.…”
Section: Discussionsupporting
confidence: 64%
“…Consistent with strategic choice theory (e.g., Child 1972;Hrebiniak and Joyce 1985;Oliver 1991) and the premise that CEO leadership plays a pivotal role in the adoption of organizational diversity practices (e.g., Ng 2008;Mighty 1996), results from this study suggest that both CEO transformational and transactional leadership influence the extent to which organizational diversity practices are implemented in organizations. Specifically, transformational leadership was found to be directly positively associated with the implementation of organizational diversity practices, while the influence of transactional leadership on organizational diversity practices was moderated by the social values and age of the CEO.…”
Section: Discussionsupporting
confidence: 64%
“…The voluntary adoption of diversity management practices is an example of strategic managerial choice. For example, although institutional factors may pressure organizations to implement EEOs and AAPs, organizational decision-makers exercise discretion as to whether and how to manage diversity (Mighty, 1996). Miles and Snow (1978) identified three characteristics of the strategicchoice perspective.…”
Section: Strategic Choice Theorymentioning
confidence: 99%
“…The self-interest hypothesis (Bell, Harrison, & McLaughlin, 1997) suggests that an individual's attitude will be shaped largely by positive expected outcomes that satisfy one's self-interests. Mighty (1996) also suggested that female leaders are also more likely to have experienced systematic discrimination themselves or to be more aware of the disadvantages women face in employment because of their gender. Although it is possible for women who have gained prominence in management ranks to deny that there was systemic discrimination against women, a phenomenon known as the "queen bee syndrome," and are consequently reluctant to assist other women (Rindfleish, 2000), research studies have concluded that a majority of women do not hold such views.…”
Section: Gendermentioning
confidence: 99%
See 2 more Smart Citations